Development of an IoT-Based Anthropometry Tool with Area Mapping for Stunting Detection in Toddlers (Weight) - NAHAL, KLAUDIA (Jurnal Teknokes, 2024)
Stunting is one of the child nutrition health problems in Indonesia. Children who experience stunting tend to have abilities below the average child of their age. The purpose of this research is to develop a web-based infant and toddler nutrition monitoring system using z-score calculations and equipped with regional mapping in Gubeng sub-district. The weight module uses a load cell sensor as a weight sensor connected to the HX711 module as a converter and amplifier and ESP 32 as a microcontroller. This web is equipped with mapping of the Gubeng sub-district area with the K-Means method.  Another feature is also a gmail notification that will automatically go to the email of officers and parents. The results show that this module and system are able to measure the weight of infants and toddlers and are able to analyze nutritional status through calculations with the z-score method.  The whole module and system are expected to help health workers and health offices in monitoring the nutritional conditions of infant and toddler growth and the spread of stunting cases in Gubeng District.